2014
DOI: 10.1021/cm500805c
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Functionalized Carbon Nanotubes with Pyridine Groups as Easily Tunable N-Decorated Nanomaterials for the Oxygen Reduction Reaction in Alkaline Medium

Abstract: We report on the N-decoration of multiwalled carbon nanotubes (MWCNTs) via chemical functionalization under mild reaction conditions. The introduction of tailored pyridinic functionalities as N-containing edge-type group mimics generates effective catalysts for the oxygen reduction reaction (ORR) in an alkaline environment. The adopted methodology lists a number of remarkable technical advantages, among which is an easy tuning of the electronic properties of N-containing groups. The latter aspect further incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(112 citation statements)
references
References 93 publications
3
109
0
Order By: Relevance
“…54 A lot of experimental results prove pyridinic-N is ORR active. 27,28,43,55,56 In our case, the pyrrolic-N is excluded as the most active site due to the observation that the activity increases with the decrease of pyrrolic-N atomic content ( Figure 4b). Our results shows that the primary activity comes from both graphitic-N and pyridinic-N but we can't distinguish between them, because the trend is similar showing the ORR activity increases with the increase of graphitic-N and pyridinic-N atomic content except for CNNT-ACN (Figure 4b).…”
Section: Resultsmentioning
confidence: 90%
“…54 A lot of experimental results prove pyridinic-N is ORR active. 27,28,43,55,56 In our case, the pyrrolic-N is excluded as the most active site due to the observation that the activity increases with the decrease of pyrrolic-N atomic content ( Figure 4b). Our results shows that the primary activity comes from both graphitic-N and pyridinic-N but we can't distinguish between them, because the trend is similar showing the ORR activity increases with the increase of graphitic-N and pyridinic-N atomic content except for CNNT-ACN (Figure 4b).…”
Section: Resultsmentioning
confidence: 90%
“…Based on this fundamental concept, the chemical functionalization becomes an alternative and effective approach to introducing N into complex carbon nanostructures [80]. Accordingly, Tuci et al reported a systematic study on the synthesis, characterization, and electrocatalytic property of MWCNTs functionalized with a series of well-defined pyridine groups [81]. They also discussed the role of the electronic charge density distribution at the chemically grafted N heterocycles on the ORR performance.…”
Section: Ncnts As a Metal-free Catalyst For Orrmentioning
confidence: 99%
“…However, as one of the scarcest noble metals on Earth, the major concern for all existing and emerging applications built upon Pt is its limited availability and high cost [5]. In addition, Pt-based electrocatalysts suffer from other limiting factors, such as declining activity caused by methanol poisoning and instability under extreme electrochemical condition [6]. As a result, intensive research efforts have been focused on developing non-precious metal-based or metal-free ORR electrocatalysts with high activity comparable to Pt and superior stability [7,8].…”
Section: Introductionmentioning
confidence: 99%